Management & HRM practice/approach of Pidilite Specialty Chemicals (BD) Pvt. Ltd. - Akib, Ashfaq Hossain (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.